2020
DOI: 10.3390/pharmaceutics12100956
|View full text |Cite
|
Sign up to set email alerts
|

The Encapsulation of Febuxostat into Emulsomes Strongly Enhances the Cytotoxic Potential of the Drug on HCT 116 Colon Cancer Cells

Abstract: Febuxostat (FBX) is a drug able to inhibit xanthine oxidase and reduce uric acid production commonly used for the treatment of hyperuricemia in subjects suffering from gout. Several studies have also been directed at its use as anti-cancer drug during the last years, opening a window for its off-label use. In the present study, an optimized formulation in terms of vesicle size and drug release, obtained by encapsulation of FBX into the emulsomes (FBX-EMLs), was evaluated for its cytotoxic potential in human co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Their findings revealed that EMLs surface modification with a crystalline S-layer lattice protected cells from oxidative stress and membrane damage. Researches conducted in our laboratory have explored the utilization of EMLs in enhancing the cytotoxic and pro-apoptotic effects of statins, Piceatannol and febuxostat [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that EMLs surface modification with a crystalline S-layer lattice protected cells from oxidative stress and membrane damage. Researches conducted in our laboratory have explored the utilization of EMLs in enhancing the cytotoxic and pro-apoptotic effects of statins, Piceatannol and febuxostat [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of cell cycle in OVCAR3 under our experimental conditions was performed by using flow cytometry as previously described ( Alfaifi et al, 2020 ; Fahmy and Aldawsari, 2020 ). Briefly, OVCAR3 cells, previously seeded in 96-well plates (3 × 10 5 cells/well), were treated with MEL, FLV-R, or FLV-MEL nano-conjugates for 24 h. Untreated cells were considered as a control.…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative determination of BAX and BCL-2 proteins was carried out after 24 h treatment by using Human BAX ELISA kit (DRG Instruments GmbH, Marburg, Germany) and Zymed ® Bcl-2 ELISA Kit, respectively, according to the manufacturers’ instructions ( Fahmy and Aldawsari, 2020 ; Md et al, 2020 ). Untreated cells were considered as a control.…”
Section: Methodsmentioning
confidence: 99%
“…The cell cycle DNA distribution was determined using a FACS Calibur flow cytometer instrument (BD Bioscience, San Jose, CA, USA) as previously described [ 50 , 51 , 52 ]. In brief, many plates (6-well cell culture) were utilized and seeded with about 5 × 10 3 A549 cells per well.…”
Section: Methodsmentioning
confidence: 99%